2006
DOI: 10.1002/cne.21096
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of muscarinic acetylcholine receptors across excitatory and inhibitory cells in visual cortical areas V1 and V2 of the macaque monkey

Abstract: Cholinergic neuromodulation, a candidate mechanism for aspects of attention, is complex and is not well understood. Because structure constrains function, quantitative anatomy is an invaluable tool for reducing such a challenging problem. Our goal was to determine the extent to which m1 and m2 muscarinic acetylcholine receptors (mAChRs) are expressed by inhibitory vs. excitatory neurons in the early visual cortex. To this end, V1 and V2 of macaque monkeys were immunofluorescently labelled for gamma-aminobutyri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
144
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 89 publications
(170 citation statements)
references
References 80 publications
22
144
3
Order By: Relevance
“…8B). Consistent with this, mAChR proteins (m1 and m2) have been observed in cells throughout cortical layers in macaque V1 (Disney and Aoki 2008;Disney et al 2006;Mrzljak et al 1993), suggesting that m1-and m2-AChRs play important roles in facilitatory modulation. It remains to be clarified, however, how this facilitatory effect is mediated by mAChRs in the neuronal circuitry of V1.…”
Section: Facilitatory Ach Effect In V1supporting
confidence: 68%
See 2 more Smart Citations
“…8B). Consistent with this, mAChR proteins (m1 and m2) have been observed in cells throughout cortical layers in macaque V1 (Disney and Aoki 2008;Disney et al 2006;Mrzljak et al 1993), suggesting that m1-and m2-AChRs play important roles in facilitatory modulation. It remains to be clarified, however, how this facilitatory effect is mediated by mAChRs in the neuronal circuitry of V1.…”
Section: Facilitatory Ach Effect In V1supporting
confidence: 68%
“…8B; n ϭ 47). An antagonistic effect by At was observed across all cortical layers, which is consistent with the expression of mAChR proteins (Disney and Aoki 2008;Disney et al 2006). We estimated laminar differences in the relative contribution of non-mAChRs by calculating their mean percentage contribution in each layer.…”
Section: Receptor Subtypes Mediating the Facilitatory Ach Effectsupporting
confidence: 59%
See 1 more Smart Citation
“…In fact, it has been observed that spiking reliability in the LGN is also enhanced following BF electrical stimulation (Goard and Dan 2009). However, this effect could also be mediated by V1 infragranular layer neurons, which express mAChR (Disney and Aoki 2008;Disney et al 2006) and are the main source of LGN top-down modulatory inputs (Fitzpatrick et al 1994). It thus remains possible that the LGN effects are a consequence and not the cause of V1 reliability modulations following BF stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Cholinergic receptor distribution on different cells varies between V1 and V2 (Disney et al, 2006). Therefore, extrapolation of the role of ACh in V1 to higher cortical areas might be misleading.…”
Section: Introductionmentioning
confidence: 99%